Large-scale periodic pattern in homeotropic liquid crystals induced by electric field. Issue 1 (2nd January 2019) - Kósa, Tamás; Coutino, Pedro; Munoz, Antonio; Taheri, Bahman; Jánossy, István
ABSTRACT: In-plane periodic modulation of the director field of an initially homeotropic liquid crystal layer with negative dielectric anisotropy is studied in external electric field with time varying amplitude envelope. Periodically turning a low frequency electric field on and off the cell, an in-plane periodic modulation of the director develops with a length scale that is orders of magnitude larger than the cell gap and can be as large as couple of centimetres. Doping the liquid crystal layer with low concentration of dichroic dye allows easy mapping of the director. We show that the periodic pattern is a periodic arrangement of +1 and −1 point defects, so called 'umbilics'. We argue that the in-plane direction of the director is governed by the local flow that accompanies the turn on and off of the electric field. The finite size and the shape of the cell, incompressibility constraint and the nature of the surface alignment material, all together with the flow, are ultimately responsible for the development of the observed periodic director modulation. GRAPHICAL ABSTRACT: